Проблеми формування національної армії в УНР (березень 1917 – квітень 1918 рр.) - Логвиненко, І. А.; Lohvynenko, I. A.; Логвиненко Ігор Альбертович (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 3(74). - С. 43–49, 2016)
Досліджено основні етапи та напрями національного військового будівництва доби Української Центральної Ради. Зазначено, що Лютнева революція 1917 року стала своєрідним каталізатором, який прискорив демократичні процеси в російській армії, дав поштовх стихійній українізації військових частин. З’ясовано позитивні т негативні наслідки демократизації та українізації армії, та ставлення керівництва УЦР до цих процесів і до створення національної армії. Охарактеризовано другий етап військового будівництва в Української Народної Республіці. Проаналізовано досвід формування національного війська в УНР. Зроблено висновок, що гарантом політичної, економічної, культурної незалежності держави має бути боєздатна, добре організована, належним чином озброєна армія, яка спирається на підтримку народу та захищає незалежність і територіальну цілісність України.

The basic stages and directions of the national military building of the period of Ukrainian Central Rada have been researched. It has been indicated that the February revolution of 1917 became a catalyst that accelerated the democratic processes in the Russian army, gave impetus to spontaneous Ukrainianization of military units. The effects of the processes of democratization and Ukrainization of the army have been demonstrated. The author has provided the estimation of the views and attitudes of the leaders of Rada to these processes, their involvement in the creation of the national army. The second stage of military building in the Ukrainian People’s Republic has been analyzed, which is characterized by unsuccessful attempts of the socialist majority of Rada to create Ukrainian army on voluntary principles. Both positive and negative experience of the formation of the national army in the Ukrainian People’s Republic has been researched. It has been concluded that the guarantor of political, economic and cultural independence of the state is to be capable, well-organized, properly armed army, which is supported by the people and protects the independence and territorial integrity of Ukraine.

Исследованы основные этапы и направления национального военного строительства периода Украинской Центральной Рады. Указано, что Февральская революция 1917 года стала своеобразным катализатором, который ускорил демократические процессы в российской армии, дал толчок стихийной украинизации воинских частей. Выяснены позитивные и негативные последствия демократизации и украинизации армии, отношение руководства Украинской Центральной Рады к этим процессам и к созданию национальной армии. Охарактеризован второй этап военного строительства в Украинской Народной Республике. Проанализирован опыт формирования национального войска в УНР. Сделан вывод, что гарантом политической, экономической, культурной независимости государства должна быть боеспособная, хорошо организованная, должным образом вооружённая армия, которая поддерживается народом и защищает независимость и территориальную целостность Украины.
Problems of forming the national army in the Ukrainian People’s Republic (March, 1917 – April, 1918)
Проблемы формирования национальной армии в УНР (март 1917 – апрель 1918 рр.)
Keywords: Держава і право. State and Law. Государство и право; Історія. History. История; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Українська Центральна Рада; Українська Народна Республіка; Український генеральний військовий комітет; українізація; армія; народна міліція; військове управління; Ukrainian Central Rada; Ukrainian People’s Republic; Ukrainian General Military Committee; ukrainization; army; people’s militia; military administration; Украинская Центральная Рада; Украинская Народная Республика; Украинский генеральный военный комитет; украинизация; армия; народная милиция; войсковое управление